2017
DOI: 10.1111/myc.12635
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal prophylaxis in newly diagnosed AML patients–Adherence to guidelines and feasibility in a real life setting

Abstract: Antifungal posaconazole prophylaxis for AML patients receiving induction chemotherapy has been routine at our centre since 2009. This retrospective study examined the feasibility and practicability of our prophylaxis guidelines in clinical practice. Data sets of 90 patients undergoing induction-chemotherapy for AML between 2011 and 2014 were evaluated regarding adherence to local guidelines for the administration of antifungal prophylaxis with posaconazole. 75.5% of the 90 patients received posaconazole prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The primary documented rationales for early discontinuation were elevated liver function tests, an inability to take an oral formulation, and drug cost. There were no significant differences in the frequency or distribution of the rationale for early discontinuation between formulations, which is consistent with the findings reported from previous studies ( 9 , 21 ). Evaluation of the clinical outcomes of patients that discontinued posaconazole was beyond the scope of this study, but they should be explored to better understand the relative trade-offs between those outcomes and the rationale for discontinuation.…”
Section: Discussionsupporting
confidence: 92%
“…The primary documented rationales for early discontinuation were elevated liver function tests, an inability to take an oral formulation, and drug cost. There were no significant differences in the frequency or distribution of the rationale for early discontinuation between formulations, which is consistent with the findings reported from previous studies ( 9 , 21 ). Evaluation of the clinical outcomes of patients that discontinued posaconazole was beyond the scope of this study, but they should be explored to better understand the relative trade-offs between those outcomes and the rationale for discontinuation.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that antifungal prophylaxis with posaconazole significantly reduced IFIs and the need for antifungal treatment. Several recent studies supported the finding that posaconazole prophylaxis reduces the incidence of IFIs and invasive aspergillus in patients with AML/MDS or hematopoietic cell transplantation recipients when tested against comparable antifungal agents [ 16 , 17 , 18 ]. Prophylactic posaconazole was associated with statistically significantly fewer febrile days, shorter duration of hospitalization, and longer fungal-free survival; however, overall and attributable mortality did not differ [ 19 ].…”
Section: Discussionmentioning
confidence: 93%
“…presented inadequacies in indication (16%), drug selection (31%) and dosing (16%) of antifungal agents in medical departments, haematology/oncology and intensive care units. Berking et al . documented non‐adherence to guidelines in 24.5% of patients with AML receiving POS prophylaxis.…”
Section: Discussionmentioning
confidence: 99%